Optimalisasi Hasil Penangkapan Ikan Untuk Meningkatakan Perekonomian Mitra Binaan Nelayan Desa Bandengan Kendal - Adenanthera Lesmana Dewa; Lisda Rahmasari (Pusat Riset dan Inovasi Nasional, 2021)
The standard of living of the fishermen in Bandengan Village in general still lives below the poverty line. The condition of the houses which are semi-permanent as permanent residences even though the houses are close to each other accompanied by an environment that is still dirty and the unpleasant smell of fish waste whose drainage is not smooth adds to the poor environment. Healthy . Due to the slum and unhealthy environmental conditions, the fishermen of Bandengan Village are still able to survive in order to make a living even though they only fish to meet their daily needs.Regarding the position of deeper sea depths, generally fishermen have not been able to determine the exact position of fishing areas or have not mapped out exactly which areas have deeper depths and are thought to have lots of fish. From the data obtained, most of the overall fish catches have not increased. From the results of the analysis, this is because half of the fishing groups' fish catches have increased and half of the fishing groups' fish catches have experienced a decrease.Therefore, AMNI Maritime University has made the fishing community in Bandengan Kendal Village a Development Partner in order to improve the economy of the fishing community through optimizing fishing.